2023
DOI: 10.3389/fcell.2023.1201200
|View full text |Cite
|
Sign up to set email alerts
|

AnnexinA6: a potential therapeutic target gene for extracellular matrix mineralization

Jie Yang,
Tong Pei,
Guanyue Su
et al.

Abstract: The mineralization of the extracellular matrix (ECM) is an essential and crucial process for physiological bone formation and pathological calcification. The abnormal function of ECM mineralization contributes to the worldwide risk of developing mineralization-related diseases; for instance, vascular calcification is attributed to the hyperfunction of ECM mineralization, while osteoporosis is due to hypofunction. AnnexinA6 (AnxA6), a Ca2+-dependent phospholipid-binding protein, has been extensively reported as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 198 publications
0
0
0
Order By: Relevance
“…Although cargos of the pro-calcified EVs is not explored in this study, it has been shown that sphingolipid phosphodiesterase 3, phosphatidylserine, annexin A6, and microRNAs (e.g. miR143, miR221, and miR222) contained in EVs are the potential mediator for other cells calcification 58 - 60 . Previous studies have shown that externally added VSMC-derived EVs induce phenotypic switching under oxidative stress 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Although cargos of the pro-calcified EVs is not explored in this study, it has been shown that sphingolipid phosphodiesterase 3, phosphatidylserine, annexin A6, and microRNAs (e.g. miR143, miR221, and miR222) contained in EVs are the potential mediator for other cells calcification 58 - 60 . Previous studies have shown that externally added VSMC-derived EVs induce phenotypic switching under oxidative stress 20 .…”
Section: Discussionmentioning
confidence: 99%